The understanding about the concept of house loan and house financing contract / Zaim Hamidi Roslee - Roslee, Zaim Hamidi (2019)
Nowadays, people in Malaysia already have potential of buying new house because it is living needs. There are many housing loan companies which provide different type of loans with different type of factors. As the banks provided in Malaysia, there are several types of contract and that becomes the differentiate among Conventional banks and Islamic banks. This paper will discuss about the concept of house loan and house financing contract, the tendency of people in selecting the contract and encouraging the people to use the Islamic contract. This research was conducted using a survey method by distributing questionnaires to achieve the research’s objective. The data was collected among the staff in Academy of Contemporary Islamic Studies UiTM Puncak Alam. The research is important to get if the respondents are understanding about the concept of house loan and house financing contract. The outcome of this research found that most of the respondents are understand about the concept of house loan and house financing contracts.